Integration of Disaster Education and Social Entrepreneurship in The Development of Educational Tourism After The Mount Semeru Eruption : Rebuilding Learning and Livelihoods - Indratmoko, J. Agung; Prasetiyorini , Pudhak (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to analyze the integration of disaster education with the development of educational tourism as a holistic post-disaster recovery strategy. Using a qualitative approach with a case study design, the data were collected through in-depth interviews with 25 purposively selected participants—teachers, students, community leaders, and government representatives—alongside field observations and document analysis conducted in the Pronojiwo and Candipuro Districts of Lumajang Regency. Data were analyzed using thematic analysis following Braun and Clarke’s framework, supported by triangulation and member checking to ensure validity. The findings reveal five key aspects: (1) A gap between the national curriculum and the contextual needs of disaster education; (2) The potential of community empowerment as a source of experiential learning rooted in local wisdom; (3) Increased student engagement through experiential learning based on educational tourism; (4) Local government support that is not yet accompanied by adequate coordination and policy frameworks; and (5) The emergence of a sustainable education–economy ecosystem through social entrepreneurship. This study concludes that the integration model of disaster education and educational tourism offers a double-win solution: not only restoring the education sector through a contextual approach but also driving community economic recovery. The research implications recommend the development of a local-content disaster curriculum, teacher training based on trauma-informed pedagogy, and the establishment of a multi-stakeholder collaborative forum to create a resilient and sustainable learning environment in disaster-prone areas.